Determination of mechanical properties of whey protein films during accelerated aging: Application of FTIR profiles and chemometric tools. (26th June 2020) - Agudelo‐Cuartas, Camilo; Granda‐Restrepo, Diana; Sobral, Paulo J. A.; Castro, Wilson
Abstract: Nowadays, the application of non‐destructive techniques in food engineering is arising. Fourier transform infrared spectroscopy (FTIR) combined with chemometric tools show potential in evaluation of food materials. The aim of this work was to determine the applicability of FTIR profiles and chemometric tools to predict the mechanical properties of whey protein‐based film (WPF). A WPF solution was prepared using whey protein concentrate/distilled‐water/glycerol in (10/85/5% wt/wt) respectively. Then, the films were aged at 30°C/5 days and 60% RH. Each day, 10 pieces were evaluated, obtaining their FTIR profiles (4000–650 cm −1 ), tensile strength (TS), elongation at break (EB), and elastic modulus (EM). Principal component analysis‐multilinear regression (PCA‐MLR) and partial least square regression (PLSR) were developed using the K‐fold cross‐validation technique. For EB and EM, the coefficient of correlation (R 2 ) and root means squared error (RMSE) were above 0.8990 and under 0.5250 (Full PLSR) and 0.8730 and 0.1378 (Optimized PLSR), unlike to TS presented R 2 and RMSE values lower than 0.2160 and 2.5247, similar to PCA‐MLR models with values lower than 0.2050 and 0.1889, respectively (for all variables). In this sense, the use of FTIR profiles coupled to chemometric tools could be adequate to predict some properties in WPFs during aging. Practical applications: This research presents a practical way for mechanical properties evaluation in films by means of Fourier Transform Infrared Spectroscopy (FTIR) coupled to chemometric tools. This new method could be useful for rapid monitoring of textural properties and characterization of films for food packaging. Abstract :